152 The Prevalence of Early Repolarisation Pattern in Young Indian Population. (6th June 2015) - Narain, Rajay; Sharma, Sanjay
Abstract : Background: The early repolarisation (ER) pattern has been associated with sudden cardiac death. The prevalence of this has not been described in the Indian population. Its prevalence varies in various ethnic groups. Aims and objectives: The aim of this study was to look at the incidence of ER in healthy young Indian population and compare it with other ethnic origins. Methods: ECGs were obtained from 554 apparently healthy Indian individuals attending cardiac screening. Participants completed a questionnaire stating symptoms, medical and family history, and physical activity (42% ≥ 10 hr./wk.). Individuals were aged from 12 to 35. Heart rate, QRS duration, QTc interval and voltage criteria for LVH was reported. The presence of ER was reported independently by three cardiologists (RN, GM, NK), with decisions by consensus. If required, a senior colleague (EB) adjudicated. ER was defined as J-point elevation of ≥0.1 mV in two consecutive inferior or lateral leads and classified as notched or slurred. ST segments were defined as rapidly ascending or horizontal/descending. Results: ER was seen in 52 individuals, 48% in lateral, 42% in inferior and 21% in infero-lateral leads. J waves were notched in 56% and slurred in 62%. 90% of ER was associated with a rapidly ascending ST segment. The higher mean age was also seen in lateral (20.8 ± 5.8 vs 18.1 ± 4.8), inferior (22.2 ± 6.8 vs 18.6 ± 5.2), notched (22.6 ± 8.0 vs 18.5 ± 5.2) and up-sloping ST segment (21.4 ± 6.8 vs 17.9 ± 4.7) groups. 18–35 yr olds exercised more than under 18s (62.0% vs 31.2% ≥10 h/week). ER was associated with lower heart rate and shorter QTc. ER was more common in males and the one who were physically active. Conclusion: ER is present in 9.4% of healthy young Indians. This is comparable to population studies although lower than in African Americans and athletic white Caucasians. The study population was young and active and prevalence was expected to be higher. Our study shows individuals with ER were older in contrast to previous studies that have associated ER with younger age. This may reflect the youth of our population, endocrine influences at puberty and higher exercise levels in 18–35 yr olds. There may therefore be a peak prevalence of ER in the late teenage years or early 20s. Larger studies are required.